Prognostic value of c-erbB-2 expression in uterine cervical carcinoma. Issue 7 (July 1992) - Hale, R J; Buckley, C H; Fox, H; Williams, J
Abstract : AIMS: To study the pattern of expression and prognostic importance of c-erbB-2 protein in cervical carcinoma. METHODS: Sixty two cases of stage IB/IIA cervical carcinoma, representing the three main tumour types, were investigated immunohistochemically for the presence of c-erbB-2 protein expression, using a monoclonal antibody (CB11) to its internal domain. Follow up of at least five years' duration was available in all cases. RESULTS: Definite membrane staining was seen in 38.7% of cases. There was a strong correlation with poor survival (p less than 0.0001) particularly. For those with adenocarcinomas, this was the case when nodal metastases were present. In contrast, for squamous carcinomas and adenosquamous carcinomas, the association with a poor prognosis was most apparent in those patients without lymph node metastases. CONCLUSIONS: These findings raise the possibility that immunostaining for c-erbB-2 protein could be used as a prognostic marker and may help identify those patients for whom early adjuvant treatment might be beneficial.